2013
DOI: 10.1155/2013/628572
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Breech Presentations at Term

Abstract: The authors present a case of 38-year-old laboring woman with four-time repetitive breech presentation of the fetus at term. This rare condition affects the mode of delivery and represents serious obstetrical problem as it is associated with increased perinatal morbidity or mortality. The authors give details on risk factors for breech presentation, its diagnosis, and the discussion points on possible causes leading to repetitive breeches in laboring women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
5
0
3
Order By: Relevance
“…In more than 50% of cases breech persisted from 33 weeks of gestation. 2,5 Most of the breech presentations had an aetiological factor like oligohydramnios, uterine anomalies, short cord, fetal growth restriction, prematurity unlike other studies which showed etiology in only 7-15% of breech presentation. 9 Fundoanterior and fundoposterior placental positions were associated with breech in ourstudy.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In more than 50% of cases breech persisted from 33 weeks of gestation. 2,5 Most of the breech presentations had an aetiological factor like oligohydramnios, uterine anomalies, short cord, fetal growth restriction, prematurity unlike other studies which showed etiology in only 7-15% of breech presentation. 9 Fundoanterior and fundoposterior placental positions were associated with breech in ourstudy.…”
Section: Discussionmentioning
confidence: 79%
“…Short cord, seen in 2% of cases, is also a cause for breech presentation as shown by Adinma's study in which 1000 cases were observed to have short cord. 5 Recurrent breech was observed in 6%. No obvious fetal anomalies were detected in the breech cases similar to the Cameroonian study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The predisposing factors for breech presentation are uterine anomalies (e.g., uterus arcuatus, uterus bicornis, uterus duplex), uterus myomatosus, pelvic tumor, advanced multiparity, history of cesarean delivery or breech delivery, gestational diabetes, multiple gestation, congenital anomalies of the fetus (neural tube defects, fetal hydrocephalus or anencephaly), neuromuscular diseases, cephalo-pelvic disproportion, prematurity, low fetal birth weight, oligohydramnios, short umbilical cord, polar placentation, and placenta praevia [4,5]. However, in about 75% of cases, no specific cause of term breech presentation could be identified [4,6]. The main types of breech presentation are frank (≈60-70%), complete (≈4-10%), and incomplete breech (≈20-36%) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Among the various etiological factors of breech in our study the most commonl factor is prematurity (50%), followed by multiparity ((20%) polyhydraminos (4.7%) and oligohydramino (2.3%)In study done by sonali oligohydramino was seen in 3% of patients (2) , Uterine anomalies are seen in 2.3% of patients, hydrocephalus in 2.96%, idopathic in 12.94% and short cord in 4.7%. Short cord is also a cause of breech presentation as shown by Adinma's study in which 1000cases were observed to have a short cord (15) . Since Breech is also associated with fetal anomalies, oligohydramino, polyhydraminos, short cord, uterine anomalies so it is important to look for all these conditions either by USG or at the time of lscs.…”
Section: Discussionmentioning
confidence: 90%